DIZZINESS SYNDROME: ETIOLOGICAL FACTORS AND COMORBID CONDITIONS - Yakubova Marhamat Mirakramovna,; Soliyeva Odina Ulug‘bek qizi,; Rasulova Laziza Shuhratovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. This study analyzed the etiological structure, accompanying symptoms, comorbid diseases, and instrumental findings in patients presenting with dizziness syndrome. Twenty-seven patients aged 20–75 years (mean age 51.05 ± 5.24) underwent clinical-neurological assessment, brain and spinal MRI/CT, and duplex scanning of cerebral vessels. The leading causes of dizziness were chronic cerebral circulatory disorders, asthenoneurotic syndrome, vertebrobasilar insufficiency, vestibular syndrome, and cardiovascular pathology. Headache was the most frequent accompanying symptom, while hypertension and diabetes mellitus were the most common comorbidities. MRI/CT findings predominantly reflected vascular and intracranial pressure-related changes, including intracranial vertebral artery atherosclerosis, vertebral artery hypoplasia, extracranial arterial changes associated with cervical disc herniation, and signs of intracranial hypertension. The results support the need for an integrated diagnostic approach combining neurological, vascular, and systemic evaluation to improve etiological identification and management of dizziness syndrome.